2016
DOI: 10.5424/fs/2016252-09149
|View full text |Cite
|
Sign up to set email alerts
|

Carbon content of forest floor and mineral soil in Mediterranean Pinus spp. and Oak stands in acid soils in Northern Spain

Abstract: Aim of study: The aim of the study was to determine the baseline carbon stock in forest floor and mineral soils in pine and oak stands in acid soils in Northern Spain.Area of study: The study area is situated in northern Spain (42° N, 4° W) on "Paramos y Valles" region of Palencia. Material and methods:An extensive monitoring composed of 48 plots (31 in pine and 17 in oak stands) was carried out. Litter layers and mineral soil samples, at depths of 0-30 cm and 30-60 cm, were taken in each plot. An intensive mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Also, according to Lal (2005) soils under natural forest, in general, have more soil organic carbon contents than those under managed forest plantations. Herrero et al (2016), in a study carried out in northern Spain, observed similar carbon content in soils when comparing plantations of Pinus spp. with natural Quercus pyrenaica areas (53 Mg C ha −1 vs. 60 Mg C ha −1 ), these values being, however, clearly lower than those found in the present study.…”
Section: Carbon Stocks In the Mineral Soilmentioning
confidence: 70%
See 3 more Smart Citations
“…Also, according to Lal (2005) soils under natural forest, in general, have more soil organic carbon contents than those under managed forest plantations. Herrero et al (2016), in a study carried out in northern Spain, observed similar carbon content in soils when comparing plantations of Pinus spp. with natural Quercus pyrenaica areas (53 Mg C ha −1 vs. 60 Mg C ha −1 ), these values being, however, clearly lower than those found in the present study.…”
Section: Carbon Stocks In the Mineral Soilmentioning
confidence: 70%
“…At all depths, soil carbon accumulation under PM and PN species is significantly lower than that under QP species, which can be justified by several effects as site preparation (Fonseca et al, 2014;Ferré et al, 2014), management practices (Zhang et al, 2016) and the nature of the litterfall produced by each tree species (Vesterdal et al, 2013;Cools et al, 2014;Zhang et al, 2016;Fonseca and Figueiredo, 2018). These factors may promote the breakdown of soil aggregates, affect soil biological activity and, consequently, the mineralization rate of organic residues in the forest floor and of soil organic matter (Gonçalves et al, 2013;Herrero et al, 2016;Fonseca and Figueiredo, 2018). In general, carbon storage displays a vertical gradient, tending to decrease with increasing mineral soil depth.…”
Section: Carbon Stocks In the Mineral Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…The Sustainable Forest Management Research Institute (iuFOR; University of Valladolid and INIA) also has a network of permanent plots in Pinus sylvestris plantations which consisted of rectangular 30 × 20-m plots. These plots have previously been studied to quantify the C sequestration in soils and forest biomass in Pinus sylvestris stands (Herrero and Bravo 2012;Herrero et al 2016;Herrero de Aza et al 2011).…”
Section: Introductionmentioning
confidence: 99%